A debreceni agrárfelsőoktatás első 150 éve - Komlósi, István (Gerundium, 2019)
The first 150 years of Agricultural Tertiary Education in Debrecen. The Georgikon in Keszthely was founded in 1797 as the first one in the line of subsequent agricultural tertiary institutions and was followed by one in Magyaróvár in 1818. It was fifty years later – that is one and a half centuries ago – that the National Higher Institution of Agriculture opened its gates in Debrecen. The speech that opened the first academic year at the new agricultural higher school was delivered by the then director Péter Papi Balogh and it has been preserved for later generations. On 5 September 2018, a hundred and fifty years later, Dean István Komlósi had the honour to recall the first 150 years of agricultural tertiary education in Debrecen. His speech is published in full length by Gerundium, the journal devoted to papers on the history of the University of Debrecen.